Enhancing Fintech Security and Countering Terrorist Financing: A Case Study of Kenya’s Fintech Landscape - ENAME MINKO, ABRAHAM (Journal of Central and Eastern European African Studies, 2024)
This research aims to investigate the intersection of fintech security and the War on Terror within the context of Kenya’s burgeoning fintech landscape. With the rapid growth of fintech solutions in Kenya, there arises a pressing need to assess the security challenges and vulnerabilities that accompany this growth, particularly in light of the country’s ongoing efforts to combat terrorism. The research will delve into the present challenges and prospects of fintech security, with a specific focus on strategies for managing complex threats and risks associated with terrorist financing, both locally and globally. By examining the unique socio-economic and geopolitical dynamics of Kenya, this study will shed light on the critical role of fintech in national security efforts, including the detection and prevention of illicit financial activities linked to terrorism.